2022
DOI: 10.1149/2754-2726/ac8aa8
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Single-Entity Electrochemical Fluoride Sensor for Fuel Cell Membrane Degradation Diagnostics

Abstract: To the best of our knowledge, very few works have been done on the continuous real-time monitoring of proton exchange membrane fuel cells (PEMFCs) membrane degradation based on fluoride-specific electrochemical microsensors. PEMFCs are eco-smart energy sources for efficient transportation but experience variable degradation rates that wear the membrane electrode assembly (MEA), a critical component of the fuel cell's functionality. Current market options lack specific diagnostics and legitimate indication of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…18,19 Lopez et al work focussed on assembling a sensor for estimating MEA degradation continuously by specifically checking fluoride focus in effluent water, a mark PEMFCs debasement status, through functionalized LaF 3 :(Au nanoparticle) thin films (∼60 nm). 20 The mass creation capacity managed the cost. In another study it was found that 3D-printing offers an interesting and captivating manufacture convention for growing minimal expense sensors which could be integrated rapidly and consistently by drug organizations or local area-based drug stores.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Lopez et al work focussed on assembling a sensor for estimating MEA degradation continuously by specifically checking fluoride focus in effluent water, a mark PEMFCs debasement status, through functionalized LaF 3 :(Au nanoparticle) thin films (∼60 nm). 20 The mass creation capacity managed the cost. In another study it was found that 3D-printing offers an interesting and captivating manufacture convention for growing minimal expense sensors which could be integrated rapidly and consistently by drug organizations or local area-based drug stores.…”
Section: Introductionmentioning
confidence: 99%
“…5 Expensive and time-consuming chromatographic systems and the need for trained personnel are among the barriers to the widespread use of these methods. [6][7][8][9] The development of simpler and faster analytical methods is important for the sensitive detection of pharmaceuticals such as paracetamol. 10 Electrochemical sensors, which can be used as an alternative application, have been frequently used in the detection and determination of pharmaceuticals in recent years due to their ease of preparation, portability, low cost and high accuracy.…”
mentioning
confidence: 99%
“…In the event that thiocyanate ion in human body is higher than ordinary, protein dialysis may be influenced and this can bring about in coma. [15][16][17][18][19][20][21][22][23] This makes selective thiocyanate determinations especially in biological fluids is an important issue. 24 ISEs for monitoring SCN − ion have been suggested, thiocyanate selective solid state electrodes showed a large interference from S 2− and I − .…”
mentioning
confidence: 99%